NILAI MORAL DALAM LEGENDA BATU GANTUNG SASTRA LISAN BATAK TOBA - Turnip, Lamria; Syam, Christanto; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is motivatedÂ by the desire of researcher of find the moralÂ value in a collection of sastra lisan short stories by Batak Toba work is dividet into four problems, namely how the moral values deficted from human relationships with God, how is the moral value depicted from humanrelationships with other human being, how is the moral value depicted from human relationship with it self, and how the plan of implementation of moral value in a collection of Batu Gantung short story by Sastra Lisan Batak Toba on learning Indonesian language at school. This study aims to obtain a picture of the moral value in a collection of sastra lisan short stories by Batu Gantung Sastra Lisan Batak Toba. The benefits of research that can be obtauned from this research, namely the benefist of theori about moral value and short story. Researcher used descriptive and qualitative methods. The approach used, namely the approach of the literary work. The source of data in this study related to the moral value that seen from human relationship with divinity, the moral value seen from human reletionship with other human beings, and phrase, and sentences in a collection of Batu Gantung short story by sastra lisan Batak Toba. Keywords: moral values, thecollection of short stories, batu gantung